1991
DOI: 10.1200/jco.1991.9.11.2021
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chemotherapy-induced anemia with recombinant human erythropoietin in cancer patients.

Abstract: Thirty patients with chemotherapy-induced anemia were treated with recombinant human erythropoietin for 4 weeks. In this dose-escalation study, cohorts of five to eight patients were treated per dose level. The doses of erythropoietin were 25, 50, 100, 200, or 300 IU/kg/d given intravenously for 5 days each week. Of 30 patients, 15 (50%) had a greater than 10% increase of their hemoglobin (Hb) values and were considered responders. At the two highest dose levels, 11 of 13 patients (85%) responded. In the 15 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(38 citation statements)
references
References 13 publications
1
37
0
Order By: Relevance
“…Most of rHuEPO studies are related with adult cases. 2,[5][6][7]11,12 Firstly, Miller and coworkers 5 mentioned that adult patients who had received high rHuEPO doses (100 -200 IU/ kg) showed a good response. Dunphy et al 6 reported that the rHuEPO dose should be increased in patients who used paclitaxel and carboplatin if the response was inadequate with 150 IU/kg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of rHuEPO studies are related with adult cases. 2,[5][6][7]11,12 Firstly, Miller and coworkers 5 mentioned that adult patients who had received high rHuEPO doses (100 -200 IU/ kg) showed a good response. Dunphy et al 6 reported that the rHuEPO dose should be increased in patients who used paclitaxel and carboplatin if the response was inadequate with 150 IU/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies recommend 150 to 300 IU/kg rHuEPO for 4 to 8 months. [5][6][7] There are only a few controlled trials in children and no precise data about the optimal dose and duration of rHuEPO treatment is available. 8 -10 The aim of our study is to investigate the efficacy and safety of rHuEPO in chemotherapy-induced anemia in children.…”
mentioning
confidence: 99%
“…Recombinant erythropoietin (r-HuEPO) has previously been shown to increase the haematocrit and reduce the transfusion requirement in patients with end-stage renal disease undergoing haemodialysis (Esbach et al, 1989) and in AIDS patients treated with zidovudine (Fischl et al, 1990). In addition, there are now a number of reports on the use of r-HuEPO to correct anaemia in cancer patients (Platanias et al, 1991;Abels, 1992aAbels, ,b, 1993Miller et al, 1992;Case et al, 1993;Lavey and Dempsey, 1993;Ludwig et al, 1993Ludwig et al, , 1994Vijayakumar et al, 1993;Dusenbery et al, 1994;Leitgeh et al, 1994;deCampos et al, 1995). In the largest randomized trial published to date, Abels (1993) demonstrated that r-HuEPO corrected anaemia and reduced transfusion requirements compared with a control group for patients with a variety of cancers undergoing chemotherapy.…”
mentioning
confidence: 99%
“…Administration of EPO has convincingly been shown to increase haematocrit and decrease transfusion requirement in 40-70% of patients with chronic anaemia of cancer [8,9]. It also prevents or ameliorates anaemia in patients undergoing chemotherapy with or without cisplatin [8,10] and improves haemoglobin levels in HIV infected patients experiencing anaemia while receiving zidovudine treatment [11]. EPO reduces red cell transfusion requirements in patients undergoing allogeneic bone marrow transplantation [12] but not in those subjected to transplantation of autologous bone marrow or peripheral blood stem cells.…”
Section: Clinical Application Of Erythropoietin In Chronic Anaemia Ofmentioning
confidence: 99%